Towards the provision of ARH medical services in selected municipalities in Aklan: From the eyes of selected LGU and frontline health workers - Remaneses, Carol Joy Palma (Animo Repository, 2006)
This study examined the perceptions of selected local government officials, health workers, and representatives from the community sector on the provision of medical services to address adolescents reproductive health needs. It also looked at how personal/individual factors like sex, age, educational attainment and religious affiliation influenced ones perception. The factors that could hinder or facilitate its provision at the local level like socio-cultural, political and economic were also explored. It also dealt with the prospects of having such services in the province of Aklan. This study is a descriptive qualitative research utilizing in-depth interview among 17 respondents grouped according to sectors: LGU, health sector and community sector, which was conducted in three municipalities of Aklan namely, Banga, Kalibo, and Makato. There were six (6) local government officials, seven (7) health workers, and four (4) community representatives interviewed in this study. A non-probability sampling, particularly the purposive sampling technique was utilized. The study used three sets of interview schedule for the three sectors interviewed. All sectors perceived ARH medical services as an important program since it addressed the adolescents RH needs; lessened the incidence of teenage pregnancy; and helped the development of youth. Some respondents across the three sectors though opposed the provision of contraceptives but all sectors still recommended that it should be included among the constellation of ARH medical services. All sectors identified teenage pregnancy, STDs and early engagement in sex as RH problems that adolescents experience today. Yet, the Banga RHU had no program to address such problems. Makato had the ARH program, but the RHU had no separate component to handle adolescents medical needs. Adolescents went to Cayangwan Tambayan Center to avail counseling and contraceptives (condoms) as provided by a core of trained peer educators. Furthermore the study showed that across the three sectors, the oldest among the group, the males, those who acquired highest educational attainment and held key positions opposed the provision of contraceptives to adolescents. Across the three sectors strong conservatism on sex and sexuality was perceived as a hindering sociocultural factor. Religion was also mentioned but had weak influence over policy making and program planning in the province. Health was not the priority of the Bangas LGU but respondents across all sectors believed that the local government would support the implementation of ARH medical services at the local level. They foresee that it could have problems regarding with its sustainability and IRA was cited as a possible source of funds. Makato LGUs main thrust was RH. Its ARH program is currently funded by UNFPA. Legislations were passed to secure funding and these resolutions allocated funds from barangay to municipal level, including funds of SK Federation. All sectors mentioned health personnel as a facilitating factor for the implementation of ARH medical services. All sectors were also convinced that ARH medial services can be implemented in the province and have identified the health personnel, LGU and the SK federation as initiators of such services. All stakeholders and the community must be involved from the planning stage up to the implementation stage of the program. Funds must be ensured too.